The Digital Sociology as a New Practice and Standard in Teaching of Sociology - Hristova, Marieta (Research Papers, 2018)
The study is dedicated to the development of digital sociology as a part of sociological science.The main tasks of this study are: to track the development of digital sociology as part of sociological science; to trace what academic disciplines are taught in sociology programmes related to internet, digital world, social media, online research methods and others at universities around the world; in which universities digital sociology is taught; to justify the necessity of introducing digital sociology as a discipline in sociology education in Bulgarian universities. I express the view that such discipline is necessary because it will react directly to the changing social world, now characterized by „big data“ and digital transformation of different kind. The digital world should became a key feature of sociological research and analysis considering the ways in which digital technologies have penetrated our everyday life and become so important to how people gather information and socially connect with others.